Damage to sheet blades of small-leaved lime of larvae of the lime leaf miner in the green stands of the Central Botanical Garden National Academy of Sciences of Belarus in 2015–2019 - Sinchuk, Aleh V.; Buga, Sergey V. (Journal of the Belarusian State University. Ecology, 2020)
Studies on damage of small-leaved lime (Tilia cordata Mill., 1768; Malvaceae) by invasive alien species, lime leaf miner (Phyllonorycter issikii (Kumata, 1963); Lepidoptera: Gracillariidae: Lithocolletinae), were carried out in the Central Botanical Gardens of the National Academy of Sciences of Belarus in Minsk throughout 2015–2019. During the period after the end of development of the first generation larvae, in the lower part of crowns less than 15% of leaf blades were inhabited, but after the end of development of the second generation larvae more than 51 % of ones were colonized by the miner. The values of the parameter in some cases varied significantly. The number of individual mines of Ph. issikii on leaf blades of T. cordata during the period after completion of development of larvae of the first generation varied from 1 to 6 per leaf, after completion of development of larvae of the second generation – from 1 to 19 per leaf, statistically significant (p<0.05) differences between them registered every year. The square of individual mines of the first generation larvae was statistically significantly larger than the ones of the second generation larvae in 2015, 2017 and 2018. The total area of individual mines on separate leaf blades after the completion of larval development of the first generation of lime leaf miner, varied by year, the minimum values were registered in 2015 (0.97 ± 0.06 cm2), the maximum values in 2018 (1.51 ± 0.10 cm2). After the completion of larval development of the second generation, the minimum values were registered in 2016 (1.45±0.13 cm2) and the maximum in 2018 (2.90±0.27 cm2). The relative square of the damaged leaf area after the completion of larval development of the first generation of lime leaf miner in the years of research varied in the range of 3–5 %, after the completion of larval development of the second generation did not exceed 10 %. However, this level of the values corresponded to a significant decorative effect loss of plants due to easily noticeable damages of leaf blades and early (at the end of August) crown defoliation.